THE MARKET REACTION OF THE STOCK SPLIT IN INDONESIAN AND MALAYSIA SHARIA CAPITAL MARKETS FOR THE 2015-2019 PERIOD - Fadlilah Fadlilah; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the market reaction to the stock split in the market. This research uses a quantitative approach using the event study method to analyze market reactions to an event. The analysis technique uses the One Sample t-Test to see market reactions and the Independent Sample t-Test to determine whether there is a difference between the Indonesian and Malaysian Islamic capital markets with a 21-day observation period consisting of 10 days before the stock split announcement (t -10), day of stock stock announcement (t0 or t = 0), and 10 days after stock split announcement (t + 10). The results of this study, based on statistical tests with α = 5%, found a significant abnormal return around the stock split announcement on the Indonesian Islamic capital market. AAR significant as much as 4 days and CAAR significant as much as 18 days during the observation period. In the Malaysian Islamic capital market, abnormal returns were also found to be significant around the stock split announcement. AAR is significant for 3 days during the observation period, 1 day before the announcement of the stock split, during the announcement of the stock split, and 1 day after the announcement of the stock split. A significant CAAR of 19 days during the observation period. In the independent sample t-test, AAR Indonesia and Malaysia obtained sig. (2-tailed) of 0.658. In the CAAR test, Indonesia and Malaysia obtained sig. (2-tailed) of 0.563. So there is no difference between the Indonesian and Malaysian sharia capital market reactions.Keywords: Market Reaction, Stock Split, Abnormal Return, Event StudyREFFERENCE Azizah, Faradilla Zulfa. (2019). Abnormal return dan volume perdagangan saham sebagai reaksi pasar terhadap stock split emiten consumer goods di Indeks Saham Syariah Indonesia (ISSI) periode 2015-2018. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Darmadji, Tjiptono, and Hendy M. Fakhrudin. (2011). Pasar modal di Indonesia. Jakarta: Salemba Empat.Fatimatuzahra, Vita. (2014). Reaksi pasar atas penerbitan sukuk (studi pada emiten saham penerbitan sukuk periode (2008-2012). Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Ghazali, Zahiruddin, Fauziah Md Taib, and Noraini Othman. (2014). Reminiscing Stock Splits Announcement: A Malaysia Case. International Journal of Business, Economics and Management, 1(7), 136-145.Hartono, Jogiyanto. (2014). Teori portofolio dan analisis investasi. Yogyakarta: BPFE.Hasna, Chotyahani. (2010). Analisis pengaruh stock split terhadap harga saham pada perusahaan Go Public di Bursa Efek Indonesia. Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Jasmine, Aldila Vania. (2015). Reaksi atas stock split pada emiten saham syariah di BEI periode 2011-2014. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Mardani. (2015). Aspek hukum lembaga keuangan syari'ah di Indonesia. Jakarta: Kencana.Mittal, Dr. Swati. (2015). Stock Market Reactions to Announcements of Stock Splits. Journal of Management Sciences and Technology, 2(2), 52-58.P.J, Jijo Lukose, and S. Narayan Rao. (2001). The market reaction to stock splits - an emperical study, The ICFAI Journal of Applied Finance.Pebrianingrum, Fifi. (2019). Analisis reaksi pasar terhadap pengunguman penerbitan sukuk (studi kasus pada emiten yang menerbitkan sukuk dan terdaftar di Bursa Efek Indonesia periode tahun 2007-2018). Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Samudra, Suryadi, and dkk. "Analisis Efisiensi Pasar Modal Pada Indeks Saham Syariah Di Bursa Efek Indonesia. Jurnal Katalogis, 4(6), 134-142.Soemitra, Andri. (2016). Bank dan lembaga keuangan syariah. Jakarta: Kencana.Sutedi, Adrian. (2011). Pasar modal syariah sarana investasi keuangan berdasarkan prinsip syariah. Jakarta: Sinar Grafika.Tandelilin, Eduardus. (2010). Portofolio dan investasi teori dan aplikasi. Yogyakarta: Kanisiu.Wijanarko, Iguh. (2012). Analisis pengaruh pemecahan saham (stock split) terhadap likuiditas saham dan return saham (study kasus pada perusahaan yang terdaftar BEI Periode 2007-2011). Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Yosef, Bar, and lawrence D. Brown. (1977). A reexamination of stock splits using moving betas." The Journal of Finance, 32(4), 1069-1080.